Advances in therapy for Philadelphia‐positive acute lymphoblastic leukaemia of childhood and adolescence. (15th January 2016) - Bleckmann, Kirsten; Schrappe, Martin
Summary: The presence of the BCR/ABL1 fusion gene in childhood acute lymphoblastic leukaemia (ALL) is a rare finding and has been an adverse prognostic factor associated with a high risk of therapeutic failure. The current key components of treatment are intensive polychemotherapy and a BCR/ABL1 kinase domain inhibitor. This treatment approach has been applied in a few clinical trials by paediatric leukaemia study groups. Thus, this subtype of ALL serves as the first model system for truly targeted treatment. The role of haematopoietic stem cell transplantation (HSCT) is increasingly called into question, at least in a favourable, though not yet clearly defined, subset of patients. Currently, the choice of the most effective tyrosine kinase inhibitor is not yet settled, in particular, in view of potential reduction of overall treatment intensity.